Divergent roles of HDAC1 and HDAC2 in the regulation of epidermal development and tumorigenesis. (15th November 2013) - Winter, Mircea; Moser, Mirjam A; Meunier, Dominique; Fischer, Carina; Machat, Georg; Mattes, Katharina; Lichtenberger, Beate M; Brunmeir, Reinhard; Weissmann, Simon; Murko, Christina; Humer, Christina; Meischel, Tina; et al.
<x xml:space="preserve">Abstract</x> The histone deacetylases HDAC1 and HDAC2 remove acetyl moieties from lysine residues of histones and other proteins and are important regulators of gene expression. By deleting different combinations of Hdac1 and Hdac2 alleles in the epidermis, we reveal a dosage‐dependent effect of HDAC1/HDAC2 activity on epidermal proliferation and differentiation. Conditional ablation of either HDAC1 or HDAC2 in the epidermis leads to no obvious phenotype due to compensation by the upregulated paralogue. Strikingly, deletion of a single Hdac2 allele in HDAC1 knockout mice results in severe epidermal defects, including alopecia, hyperkeratosis, hyperproliferation and spontaneous tumour formation. These mice display impaired Sin3A co‐repressor complex function, increased levels of c‐Myc protein, p53 expression and apoptosis in hair follicles (HFs) and misregulation of HF bulge stem cells. Surprisingly, ablation of HDAC1 but not HDAC2 in a skin tumour model leads to accelerated tumour development. Our data reveal a crucial function of HDAC1/HDAC2 in the control of lineage specificity and a novel role of HDAC1 as a tumour suppressor in the epidermis.